2014
DOI: 10.1016/j.molonc.2014.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Sialyl Tn‐expressing bladder cancer cells induce a tolerogenic phenotype in innate and adaptive immune cells

Abstract: Immunological potency T cells CD44 Mucins A B S T R A C TDespite the wide acceptance that glycans are centrally implicated in immunity, exactly how they contribute to the tilt immune response remains poorly defined. In this study, we sought to evaluate the impact of the malignant phenotype-associated glycan, sialyl-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 47 publications
5
96
0
Order By: Relevance
“…Key strategic issues included the removal of the acetyl esters of the glycan moiety prior to the installation of the Pam 2 CysFmoc moiety, the use of a strategically chosen STn building block that has the carboxylic acid of the sialoside protected as an allyl ester which could be removed under neutral conditions without causing β-elimination of the O -glycan, and microwave-assisted solid-phase peptide. Although it has been suggested that STn can suppress immune responses, 26 we have found that a fully synthetic three-component vaccine containing this epitope can elicit potent humoral as well cellular immune responses. Furthermore, it is shown that T-cells primed by such a vaccine can be restimulated by tumor-associated MUC1, which is highly significant because such restimulation of T-cells will lead to their expansion at the site of the tumor and be more able to eliminate cancer cells.…”
mentioning
confidence: 58%
“…Key strategic issues included the removal of the acetyl esters of the glycan moiety prior to the installation of the Pam 2 CysFmoc moiety, the use of a strategically chosen STn building block that has the carboxylic acid of the sialoside protected as an allyl ester which could be removed under neutral conditions without causing β-elimination of the O -glycan, and microwave-assisted solid-phase peptide. Although it has been suggested that STn can suppress immune responses, 26 we have found that a fully synthetic three-component vaccine containing this epitope can elicit potent humoral as well cellular immune responses. Furthermore, it is shown that T-cells primed by such a vaccine can be restimulated by tumor-associated MUC1, which is highly significant because such restimulation of T-cells will lead to their expansion at the site of the tumor and be more able to eliminate cancer cells.…”
mentioning
confidence: 58%
“…Monocytes were enriched using anti-CD14 mAb-coated immunomagnetic beads and cultured, as described previously. [24]…”
Section: Methodsmentioning
confidence: 99%
“…We have previously proposed that the exceptional avidity of binding between the tandemly repeated carbohydrates of MUC1 and mannose receptors on DC does not allow their dissociation after cellular internalization and thereby MUC1 degradation [95]. It was also observed that STn+ cancer cells inhibited generation of Th1 T cells further, limiting the ability of the anti-tumor T cell response [96]. This all affects development of stronger anti-MUC1 immunity that could otherwise target the abnormal MUC1 as an antigen on tumor cells for efficient cancer immunosurveillance.…”
Section: Abnormal Muc1 In the Tumor Microenvironmentmentioning
confidence: 99%